2015
DOI: 10.2458/azu_rc.57.18355
|View full text |Cite
|
Sign up to set email alerts
|

Young, Old, and Weathered Carbon—Part 2: Using Radiocarbon and Stable Isotopes to Identify Terrestrial Carbon Support of the Food Web in an Alkaline, Humic Lake

Abstract: Carbon (C) and nitrogen (N) stable isotope analysis (SIA) has been used to identify the terrestrial subsidy of freshwater food webs. However, SIA fails to differentiate between the contributions of old and recently fixed terrestrial C and consequently cannot fully determine the source, age and biochemical quality of terrestrial carbon. Natural abundance radiocarbon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…This study is one of the few studies that have used natural 14 C to assess nutritional resource utilisation by fish Ishikawa et al, 2014;Keaveney, Reimer, & Foy, 2015). There is increasing recognition that aged forms of OM can support consumer production in aquatic ecosystems Guillemette et al, 2017).…”
Section: Using Natural Abundance Isotopes In Studies Of Ammocoete Ementioning
confidence: 99%
See 2 more Smart Citations
“…This study is one of the few studies that have used natural 14 C to assess nutritional resource utilisation by fish Ishikawa et al, 2014;Keaveney, Reimer, & Foy, 2015). There is increasing recognition that aged forms of OM can support consumer production in aquatic ecosystems Guillemette et al, 2017).…”
Section: Using Natural Abundance Isotopes In Studies Of Ammocoete Ementioning
confidence: 99%
“…There is increasing recognition that aged forms of OM can support consumer production in aquatic ecosystems Guillemette et al, 2017). For instance, Keaveney et al (2015) found evidence for utilisation of aged allochthonous nutritional sources by Daphnia spp. in a humic lake; however, algal sources and other fresh allochthonous OM contributed to fishes and other zooplankton in this same study.…”
Section: Using Natural Abundance Isotopes In Studies Of Ammocoete Ementioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the potential of combining both stable and radio isotopes, we applied the Bayesian mixing model “Food Reconstruction Using Isotopic Transferred Signals” (FRUITS) (Fernandes, Millard, Brabec, Nadeau, & Grootes, ) using isotopic values of pollans ( Coregonus pollan ), its food sources, and diet‐to‐consumer isotopic offsets according to Keaveney et al. (). As relevant food sources, we included calanoid zooplankton, chironomidae, Daphnia , and littoral invertebrates (Wilson, ).…”
Section: Future Research Effortsmentioning
confidence: 99%
“…Extensive work in Lough Erne, Ireland has similarly shown algae to be 14 C‐depleted (mean Δ 14 C = −59 ± 9‰; 490 yr equivalent age), suggesting a significant freshwater reservoir offset, presumably from inputs of weathered fossil carbonates and/or aged soil CO 2 to lake DIC (Keaveney et al 2015 a,b ). In contrast, some consumers in Lough Erne were enriched in 14 C (maximum invertebrate and fish Δ 14 C values were 0‰ and 10‰, respectively, and modern‐aged; Fig.…”
Section: δ14c Values and Apparent Ages Of Aquatic Consumer Organismsmentioning
confidence: 99%